Analysis of Summative Test at Islamic Senior High School of Insan Cendekia Kota Kendari - Salsabila, Almeira; Hanna, Hanna (Universitas Halu Oleo, 2021)
This research was accomplished to investigate the quality of summative test at the Second Year Students of Islamic Senior High School (MAN) of Insan Cendekia Kota Kendari. The design of this research was descriptive quantitative research with documentation technique to collect data. The data were analyzed using qualitative and quantitative analysis. Qualitative analysis was carried out by looking at the appropriateness of items with competency being tested to determine the content validity of the test. Quantitative analysis was carried out using the SPSS 16.0 program and Microsoft Excel to operate data regarding the level of difficulty, discrimination index, item distracters, and reliability of the test. The result revealed that quality of the test in terms of content validity had met good criteria, with the value 83% of the test items represented the basic competence and indicators as the fulfillment of content validity. The results of item analysis revealed that: 1) the biggest percentage of item difficulty was at moderate category (63%); 2) the biggest percentage of item discrimination was at sufficient category (51%); 3) the biggest percentage of item distracters was at effective category (54%); 4) reliability was categorized as good with reliability coefficient 0,757